Laparoscopic versus laparotomic appendectomy for generalised peritonis in children - Plánka, Ladislav; Starý, David; Tůma, Jiří; Macháček, Robert; Gál, Petr (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2009)
The aim of our study was to compare the results obtained with traditional versus laparoscopic appendectomy in generalised peritonitis. All patients treated for generalised peritonitis at the Department of Paediatric Surgery, Orthopaedics and Traumatology (DPSOT) were monitored, with focus on differences occurring in the postoperative period following laparoscopic or open surgeries. Our set of patients was established using medical records of patients treated at DPSOT between 2002 and 2008. The selection criteria included the basic diagnosis (peritonitis diffusa) and complex diagnostics, treatment, and follow-up care at DPSOT. In terms of the postoperative period, we observed the length of treatment at ICU, the total length of hospitalisation, leukocyte and CRP level patterns, and both early and subsequent complications. Group A consisted of 140 children who underwent open surgery. Group B consisted of 70 patients in whom laparoscopic surgery without conversion was performed. The average length of intensive care after traditional open surgery for generalised peritonitis due to acute appendicitis was 6.3 days and the length of hospitalisation was 9.5 days. The average length of intensive care in patients who underwent laparoscopic surgery was 5.8 days and the length of hospitalisation was 8.9 days. The mean C-reactive protein levels on day 6 after appendectomy were 20.1 in group A and 22.0 in group B. The levels of circulating leukocytes on the same day were 5.3 in group A and 7.1 in group B. Laparoscopic appendectomy for appendicitis in its late stage with advanced generalised peritonitis does not show increased occurrence of early or late complications compared to traditional laparotomic appendectomy. Traditional open appendectomy exhibits more late complications.
Keywords: Child; Laparoscopy; apendektomie; Appendicitis; Humans; výsledek terapie; Appendectomy; Peritonitis; laparoskopie; lidé; apendicitida; dítě; Treatment Outcome; peritonitida